2014
DOI: 10.1002/adv.21470
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Clay Particles on the Mechanical Properties and Fracture Behavior of PLA/o‐MMT Composite Films

Abstract: In this study the influence of the morphology in the polylactic acid/Cloisite30B (PLA/C30B) composites on the mechanical and fracture behavior of calendered films was evaluated. An image analysis was performed using TEM micrographs in order to complete the morphological study. The micrographs were taken from ultramicrotomic samples corresponding to the melting flow (MD) and transverse direction (TD) of the films. The image analysis showed intercalated particles and tactoids, which was in accordance to the wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
(87 reference statements)
2
15
0
Order By: Relevance
“…Indeed, a great reduction in the ductility of Al‐Mulla PA6.10 composites is not repeated in the reported PA6.10_5C sample using the same modified clay. On the other hand, a similar result on film extruded samples was already reported in PLA matrix and Cloisite 30B . This trend is extremely important for the possible use of the film in packaging application, where a great elongation before break is required.…”
Section: Resultssupporting
confidence: 83%
“…Indeed, a great reduction in the ductility of Al‐Mulla PA6.10 composites is not repeated in the reported PA6.10_5C sample using the same modified clay. On the other hand, a similar result on film extruded samples was already reported in PLA matrix and Cloisite 30B . This trend is extremely important for the possible use of the film in packaging application, where a great elongation before break is required.…”
Section: Resultssupporting
confidence: 83%
“…Previous studies showed that under the used processing conditions, all films were amorphous, according to the differential scanning calorimetry (DSC) results obtained from the first heating cycle (30-200°C) at 10°C·min -1 . On the other hand, Transmission Electronic Microscopy (TEM) analysis exhibited a homogeneous distribution of o-MMT particles, irrespective of its contents (Figure 1a), with some intercalation and exfoliation (Figure 1b) which was verified by WAXS tests [22]. A 'De-aging' thermal treatment was applied to the films in order to release internal stresses and to avoid excessive defects during sample cutting due to their pronounced brittleness.…”
Section: Introductionmentioning
confidence: 99%
“…Using similar extrusion conditions, neat PLA (PLA) films were prepared. More details on films manufacturing can be found in [22]. Previous studies showed that under the used processing conditions, all films were amorphous, according to the differential scanning calorimetry (DSC) results obtained from the first heating cycle (30-200°C) at 10°C·min -1 .…”
Section: Introductionmentioning
confidence: 99%
“…Clay systems have many possible morphologies, which include: (1) agglomerated particles, where the layers remain joined and polymer chains only interact with their surface; (2) intercalated, when the polymer chains are between the clay platelets; and (3) exfoliated, when the silicate platelets are isotropically dispersed in the polymeric matrix. 11,12 Although some researchers have reported the possible use of nanofillers in dental adhesives, their use remains a challenge due to the still limited number of fillers used for this purpose. 6 Therefore, the aim of this study was to investigate the effect of the concentration and type of organomodified montmorillonite clays in the adhesion layer on the mechanical properties of dental adhesives.…”
Section: Introductionmentioning
confidence: 99%